Racial disparities in environmental auditing - Balietti, Anca; Zeising, Tom (AWI discussion paper series, 2024)
This paper investigates the role of the U.S. Environmental Protection Agency in advancing environmental justice through monitoring and enforcement efforts mandated by the Clean Air Act. Our analysis relies on a comprehensive dataset encompassing auditing information from all environmentally relevant plants between 2000 and 2018. Leveraging county-level variation in racial composition and environmental auditing, we find a substantial and persistent reduction in the proportion of inspected plants following increases in the share of non-White population. This decline coincides with a decrease in political activism, particularly among entities typically advocating for more stringent environmental protection.
Keywords: Graue Literatur